2019
DOI: 10.26858/jiap.v9i1.9331
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Principal Supervision on Teacher Pedagogic Competencies

Abstract: The research aims to Effect of Principal Supervision on Teacher Pedagogic Competencies at Public Elementary School 237 Aletellue in Soppeng Regency.This research use quantitative methodology with correlational ex post facto design to explain the research questions. To understand the issue, this research use methodological approach (quantitative-positivistic) and scientific approach (pedagogic and psychological). The participants of this reseach are 13 teachers at Publich Elementary School 237 Aletellue. The da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
2
0
1
Order By: Relevance
“…In other words, the better Academic Supervision is able to improve Teacher Pedagogic Competence or the first hypothesis (H1) is accepted. These results at the same time support the findings which states that academic supervision has a significant positive effect on pedagogical competence (Aswinda et al, 2019;Bafadal et al, 2019;E. Istiningsih et al, 2020;Porniadi et al, 2019;.…”
Section: The Effect Of Academic Supervision On Pedagogic Competencesupporting
confidence: 88%
See 1 more Smart Citation
“…In other words, the better Academic Supervision is able to improve Teacher Pedagogic Competence or the first hypothesis (H1) is accepted. These results at the same time support the findings which states that academic supervision has a significant positive effect on pedagogical competence (Aswinda et al, 2019;Bafadal et al, 2019;E. Istiningsih et al, 2020;Porniadi et al, 2019;.…”
Section: The Effect Of Academic Supervision On Pedagogic Competencesupporting
confidence: 88%
“…As a supervisor, in carrying out duties, there are several things that need to be developed for each teacher by the principal, including the personality of the teacher, continuous improvement on the profession, the learning process and mastery of subject matter. Some previous research revealed that academic supervision has a significant positive effect on pedagogical competence (Aswinda et al, 2019;Bafadal et al, 2019;A. Istiningsih et al, 2019;Porniadi et al, 2019;.…”
Section: Introductionmentioning
confidence: 96%
“…Salah satu keterampilan pendidik ahli adalah mereka harus memiliki pilihan untuk menghadapi kerangka pembelajaran yang mencakup bagianbagian yang menyertainya: target pembelajaran, materi pembelajaran, anak belajar, model dan strategi pembelajaran, aset pembelajaran dan media pembelajaran, serta penilaian. pengalaman dan hasil pendidikan (Aalto et al, 2019;Andriana et al, 2015;Aswinda et al, 2019).…”
Section: Pendahuluanunclassified
“…So, the supervision carried out by the principal on teacher performance is an integral part of evaluating the process of providing education. Teacher supervision also impacts teachers' professionalism in carrying out their main tasks and functions that develop according to science and technology (Aswinda et al, 2019). So far, supervision is also considered as a way to develop the teaching profession.…”
Section: Introductionmentioning
confidence: 99%